1987
DOI: 10.3354/meps036215
|View full text |Cite
|
Sign up to set email alerts
|

Particle clearance and yield in relation to bacterioplankton and suspended particulate availability in estuarine and open coast populations of the mussel Mytilus edulis

Abstract: Measurements were made of resource availabihty and the filtration rate and particle retention efficiency of mussels M y t h s edulis L. from an estuarine site on the River Lynher and from an open coastal site at Whitsand Bay, Cornwall, UK. Small cocci of 0.25 km, large cocci of 0.56 pm and small rods of 0.725 pm mean spherical diameter comprised 87 % of the free-living bacterial population at Whitsand Bay and 86% in the Lynher estuary during September 1984. Free-living bacteria represented only 5 % of the carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

1991
1991
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 16 publications
2
28
0
1
Order By: Relevance
“…The clearance rates obtained for P. perna in this study (from 0.16 to 0.47 l h -1 per mussel), were lower than those obtained by Resgalla Jr. et al (2006), however, these latter authors offered phytoplanktonic organisms to the mussels, so it was already expected that the clearance rates obtained by the use of bacterial cells would be lower since the size of the food offered greatly affects the results, as showed by Lucas et al (1987).…”
Section: Discussionmentioning
confidence: 42%
“…The clearance rates obtained for P. perna in this study (from 0.16 to 0.47 l h -1 per mussel), were lower than those obtained by Resgalla Jr. et al (2006), however, these latter authors offered phytoplanktonic organisms to the mussels, so it was already expected that the clearance rates obtained by the use of bacterial cells would be lower since the size of the food offered greatly affects the results, as showed by Lucas et al (1987).…”
Section: Discussionmentioning
confidence: 42%
“…This sharp decline in retention efficiency with decreasing particle size has been reported before (Lucas et al 1987;Matthews et al 1989;Ward and Shumway 2004). Preferential capture of picophytoplankton over bacteria must be based on properties other than cell size alone.…”
Section: Discussionmentioning
confidence: 81%
“…At times when total cell volume was dominated by larger cells, capture efficiency increased to larger particles (20-30 lm). Calculating the carbon per size class for data published in Lucas et al (1987) revealed a similar pattern; retention efficiency for 1.6-lm particles differed between two sites. The highest retention efficiency for these picoparticles corresponded to relative small (8 lm) particles dominating total carbon availability, while at the site with a lower retention the carbon availability was dominated by 12-to 16-lm particles.…”
Section: Variable Retentionmentioning
confidence: 81%
“…From previous studies, it was already known that adult mussels are not very efficient suspension feeders on small planktonic components like bacteria and picophytoplankton (< 2 µm), while they are generally assumed to better retain larger organisms like nanoand microsized plankton (> 2 µm) including both autotrophs and heterotrophs (Lucas et al 1987, Horsted et al 1988, Matthews et al 1989, Kreeger & Newell 1996, Ward & Shumway 2004, Trottet et al 2008a, Strohmeier et al 2012. Using a mesocosm set-up in which natural plankton was exposed to mussel filtration, we confirmed for juvenile mussels (< 25 mm) that filtration mainly affected the larger components of the plankton community (3−200 µm).…”
Section: Species Shifts and Food Web Interactionsmentioning
confidence: 99%